PERFORMANCE AND OPERATIONAL COSTS OF STRIPPING OVERBURDEN AT PT BUMI SEKUNDANG ENIM ENERGY - Puspita, M.; Wijaya, S.; Oktarinasari, E.; Mahdyrianto, F.; Erwedi (Fakultas Teknik Universitas Sriwijaya, 2025)
The plan for overburden stripping at PT Bumi Sekundang Enim Energy's Pit AB was 332,829.17 BCM/month, but the company was unable to achieve this target. This study aims to evaluate the performance of overburden stripping, identify obstacles that affect overburden stripping, and calculate the costs of overburden stripping before and after improvements are made to overcome these obstacles. This study uses a descriptive-analytical quantitative approach with a case study at PT Bumi Sekundang Enim Energy. The actual productivity of the transport equipment obtained is 20.5 BCM/hour, lower than the specified target of 22.37 BCM/hour. The failure to achieve this overburden stripping was due to obstacles that reduced effective working time and mechanical equipment efficiency. Improvements were made to delay time and idle time, successfully reducing total downtime by 40.64%. As a result, mechanical equipment efficiency increased to 77.82%. After the improvements were made, the productivity of the transport equipment increased to 25.67 BCM/hour and the overburden stripping target was achieved with a percentage of 114.76%. The operational costs of overburden stripping consist of excavation and transportation costs by mechanical equipment. The costs taken into account include fuel, lubricants and filters, tire and undercarriage replacement, ground engaging tools replacement, and operator wages. The operational cost of stripping overburden before the improvement was Rp 20,473/BCM, but after the improvement, the cost decreased by 20.14% to Rp 16,350/bcm.